Reproductive phenology of the Chesapeake Bay blue crab population in a changing climate - Schneider, Alexandra K.; Fabrizio, Mary C.; Lipcius, Romuald N. (Frontiers in Ecology and Evolution, 2024)
Global temperatures are rising across marine ecosystems in response to climate change. Marine and estuarine-dependent species including the blue crab, Callinectes sapidus, may adapt to warming temperatures phenologically, by shifting the seasonal timing of biological events, such as reproduction. In Chesapeake Bay, average water temperatures have risen by an average 0.02°C per year since the 1980s. Extension of the blue crab spawning season, through earlier onset and later conclusion, may augment annual brood production and alter the efficacy of management strategies. The duration of the potential spawning season from 1985 to 2019 was assessed using degree days, and the observed spawning season from 1995 to 2019 was assessed using the occurrence of ovigerous crabs from the Virginia Institute of Marine Science Trawl Survey in the James River and in the mainstem of lower Chesapeake Bay. Spawning degree days (SDD) and reproductive degree days (RDD) were defined using minimum temperatures of 19°C and 12°C, respectively. The mean duration of the potential spawning season increased by 25% in SDD and 10% in RDD between 1985 and 2019 in the James River and lower Chesapeake Bay, respectively. This progressive expansion of the potential spawning season was not, however, reflected in the observed spawning season. Rather, the onset, conclusion, and duration of the observed spawning season were variable over the time series. The observed month of onset was driven by RDD in spring, whereby spawning began earlier during warmer springs. The spawning conclusion date was driven by the onset of spawning, rather than Fall temperature, such that the duration of the observed spawning season and, therefore, annual brood production did not change over time. In Chesapeake Bay, the spawning stock is protected by a sanctuary that is closed to fishing from mid-May to mid-September during the putative spawning season. An earlier start to the spawning season during warmer springs, as seen in recent years, is expected to reduce the efficacy of the spawning sanctuary and intensify exploitation of the spawning stock, without enhancing brood production, thereby reducing reproductive output of the blue crab population in Chesapeake Bay.